The Reform of Christian Doctrine in the Catechisms of Peter Canisius - Flowers, Thomas, author.
1 online resource
Keywords: The catechisms of Peter Canisius reveal the contours of the struggle within the Catholic Church to reframe Christian identity in response to the Protestant Reformation. Canisius published his first catechism in 1555, and immediately achieved phenomenal publishing success. Yet his catechisms received neither endorsement nor approbation from Rome. Canisius’s catechesis proposed a confident vision of Christian identity grounded in the practice of Catholic piety. The Roman Curia increasingly conceived of catechesis as a defensive bulwark against Protestant assault. Although Canisius’s catechisms often appear in scholarship as representatives of a combative, post-Reformation style of defending Catholic orthodoxy, the combat in which they actually engaged was internal to the Catholic Church, over how to reframe post-Reformation Catholic identity.